2001
DOI: 10.1046/j.1365-8711.2001.04282.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical and infrared spectroscopy of the type IIn SN 1998S: days 3-127

Abstract: A B S T R A C TWe present contemporary optical and infrared spectroscopic observations of the type IIn SN 1998S covering the period between 3 and 127 days after discovery. During the first week the spectra are characterized by prominent broad H, He and C iiiaN iii emission lines with narrow peaks, superimposed on a very blue continuum T , 24 000 KX In the following two weeks the C iiiaN iii emission vanished, together with the broad emission components of the H and He lines. Broad, blueshifted absorption compo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
286
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 180 publications
(316 citation statements)
references
References 38 publications
30
286
0
Order By: Relevance
“…SN 1998S is unique in that it allowed the first-ever good IR spectroscopic coverage of a type IIn event [17,24]. In the J-band, we see Paschen β, Paschen γ and He I 1.083 µm lines.…”
Section: Early-time Infrared Spectral Evolutionmentioning
confidence: 85%
See 3 more Smart Citations
“…SN 1998S is unique in that it allowed the first-ever good IR spectroscopic coverage of a type IIn event [17,24]. In the J-band, we see Paschen β, Paschen γ and He I 1.083 µm lines.…”
Section: Early-time Infrared Spectral Evolutionmentioning
confidence: 85%
“…A rough blackbody fit yields T∼25,000 K, but with a blue excess [18,24]. The emission lines are identified with H I (Balmer series), He I, He II, C III and N III.…”
Section: Early-time Optical Spectral Evolutionmentioning
confidence: 96%
See 2 more Smart Citations
“…Fassia et al [16] observed narrow emission lines and inferred that the outer circumstellar medium had a velocity of 40 − 50 km s −1 . From the time evolution and velocities, they inferred that the outer wind started at least 170 years ago, stopped about 20 years ago, and the inner dense wind may have started less than 9 years ago.…”
Section: Type Iin/iil Supernovaementioning
confidence: 99%